2000
DOI: 10.1590/s0100-204x2000000400016
|View full text |Cite
|
Sign up to set email alerts
|

Tendência genética na raça Gir

Abstract: RESUMO -A importância do peso e do ganho de peso para produção de bovino de corte tem sido responsável pela grande ênfase dada a essas características pelos criadores de diferentes raças. No entanto, é importante que haja um acompanhamento dos progressos genéticos que os diferentes programas de melhoramento vêm realizando, como forma de se ter uma avaliação global da raça. Assim, o presente trabalho teve o objetivo de avaliar as tendências genéticas dos ganhos de peso pré e pós-desmama na raça Gir. Foram utili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 6 publications
0
7
0
4
Order By: Relevance
“…This effect of an increase in FP is probably related to greater inbreeding depression in milk production than in fat production. In a study using models that only included environmental effects, but not the additive genetic effect of the animal, Reis Filho () found a quadratic effect of F i on MY305, FY305 and LL. The authors observed an increase in the performance of the animals until a F i of about 10%, with a decline in performance thereafter.…”
Section: Resultsmentioning
confidence: 99%
“…This effect of an increase in FP is probably related to greater inbreeding depression in milk production than in fat production. In a study using models that only included environmental effects, but not the additive genetic effect of the animal, Reis Filho () found a quadratic effect of F i on MY305, FY305 and LL. The authors observed an increase in the performance of the animals until a F i of about 10%, with a decline in performance thereafter.…”
Section: Resultsmentioning
confidence: 99%
“…EUCLIDES FILHO et al (2000), in their study of weight gain in Gyr cattle throughout Brazil during the period between 1962 to 1994, reported that the genetic gains of the breed were low, particularly, for the post-weaning weight gain.…”
Section: Resultsmentioning
confidence: 99%
“…According to EUCLIDES FILHO et al (2000), genetic trends close to zero and even negative are not uncommon in literature, mainly where studies have used data from commercial herds where selection criteria are not well defined or uniform. BIFFANI et al (1999) suggest that in the rearing conditions typical of the northeast of Brazil, the breeders primarily select animals based on their anatomical and racial characteristics rather than on productivity.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it is necessary to know the genetic trend of the population studied (Euclides Filho et al 1997). …”
Section: Resultsmentioning
confidence: 99%